2014
DOI: 10.1111/eci.12295
|View full text |Cite
|
Sign up to set email alerts
|

Role of 9p21 and 2q36 variants and arterial stiffness in the prediction of coronary artery disease

Abstract: In these high-risk patients, 9p21 and 2q36 variants and PWV were independently associated with CAD presence and extent, but the addition of both genetic data and arterial stiffness indices to FRS did not improve the prediction of CAD compared with FRS alone. Further studies are needed to clarify the prognostic role of genetic and vascular indices in the prediction of angiographic CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…In aortic PWV studies, MI was often included in the definition of outcome variables such as overall CVD events or CHD, but not investigated as an individual outcome as has been done in this study. These previous studies show an association between aortic PWV and CHD,8, 31, 32, 33 as is shown here as well. Our results are consistent with previous PP studies that reported associations with both incident MI3 and CHD34 after adjustment for traditional CVD risk factors in a hypertensive and community‐based cohort, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In aortic PWV studies, MI was often included in the definition of outcome variables such as overall CVD events or CHD, but not investigated as an individual outcome as has been done in this study. These previous studies show an association between aortic PWV and CHD,8, 31, 32, 33 as is shown here as well. Our results are consistent with previous PP studies that reported associations with both incident MI3 and CHD34 after adjustment for traditional CVD risk factors in a hypertensive and community‐based cohort, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…For the polymorphism within the ANRIL locus, carriers of at least one A allele were significantly more prevalent in the patients than in the controls (81.7 % vs 72.7 %; OR [95% CI] 1.67 [1.35-2.05]) (Table 2). This result is in agreement with a wide list of results published previously (Palomaki et al, 2010;Hubáček et al, 2012b;Vakalis et al, 2014;Kong et al, 2018), albeit on differentially defined patients. Interestingly, in a large multicentre study (Patel et al, 2019), the same polymorphism was not associated with increased cardiovascular mortality among patients with established congenital heart disease at baseline.…”
Section: Resultssupporting
confidence: 93%
“…With regard to arterial stiffness, cfPWV was independently associated with CHD prevalence (but not AIx75). These findings are in agreement with previous studies [ 15 - 17 ]. However, a link between AIx75 and a composite endpoint of myocardial infarction, stroke, cardiac, cerebrovascular, and peripheral revascularization as well as total mortality has been reported in Austrian males (n = 520) undergoing coronary angiography [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Arterial stiffness (assessed by cfPWV) has been previously linked to the presence of coronary heart disease (CHD) [ 15 - 17 ]. Syntax score (SYNergy between percutaneous coronary intervention with TAXus and cardiac surgery) may be used to evaluate CHD complexity, severity and clinical prognosis in various patient subgroups undergoing percutaneous coronary interventions (PCIs) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%